Experiential learning as teaching strategy for entrepreneurship: assessment of a Brazilian experience. (30th October 2014) - Tete, Marcelo F.; Limongi, Ricardo; de Almeida, Marcos Inácio Severo; Borges, Cândido
As the world faces a paradigm shift driven by the growth of information technologies and knowledge, educators will need to recognise the impact of that change on entrepreneurship learning (Luczkiw, 2008). In Brazil the research on alternative methodologies for entrepreneurship education which should be utilised under this new environmental context is still incipient and has provided few empirical results. Aiming to fill this gap the paper describes and assesses an experiential entrepreneurship teaching strategy developed in a Brazilian university. The main results suggest that the method stimulated students to become future entrepreneurs and helped them to develop some entrepreneurial skills.